Effect of aerobic training on ventilatory muscle endurance of spinal cord injured men - Silva, Antônio Carlos [UNIFESP] (1998)
The functional consequences of ventilatory muscle impairment of spinal cord injured (SCI) subjects has been evaluated through spirometric and maximal respiratory pressure tests. Nevertheless, underlying functional abnormalities may be evident only under dynamic conditions, such as with a ventilatory muscle endurance test (VME). in order to evaluate the VME of thoracic SCI men and the effect of physical training on it we evaluated 12 SCI subjects (Group I) and 12 able-bodied controls (Group II). the subjects were submitted to clinical evaluation, spirometry, maximum voluntary ventilation in 12 s (MVV-12sec) and a test of VME-the highest time of sustained ventilation at 70% of the maximum voluntary ventilation in isocapnic conditions (MW-70% time). Gr. II was evaluated before and after an arm cranking aerobic training program (30 min/session, three times/week, 6 weeks) with training target heart rate corresponding to ventilatory anaerobic threshold. On the initial evaluation, Gr. I subjects presented a significantly reduced forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1) and MVV-12 sec when compared to controls (P < 0.05). Also, the VME was severely reduced in Group I (median, ranges; 1.15, 0.61-12.22) when compared to Group II (14.60, 1.20-15.00) - P < 0.001. When Gr. I subjects were separated by the level of lesion, the VME was lower in high injured (T1-T7) than intermediate (TS-TIO) and low injured patients (T11-T12) - P < 0.05. After aerobic training, Group I subjects incremented significantly the FVC (P < 0.05) and the VME (P < 0.001), so that MVV-70% time values posttraining were not different from the initial values of the Gr. II. in conclusion, (i) the VME of thoracic SCI men was severely reduced when compared to able-bodied controls; (ii) a 6-weeks arm cranking aerobic training program was efficient to normalize the VME of SCI subjects.